2015
DOI: 10.3390/catal5031352
|View full text |Cite
|
Sign up to set email alerts
|

Iron Fischer-Tropsch Catalysts Prepared by Solvent-Deficient Precipitation (SDP): Effects of Washing, Promoter Addition Step, and Drying Temperature

Abstract: Abstract:A novel, solvent-deficient precipitation (SDP) method for catalyst preparation in general and for preparation of iron FT catalysts in particular is reported. Eight catalysts using a 2 3 factorial design of experiments to identify the key preparation variables were prepared. The catalysts were characterized by electron microprobe, N2 adsorption, TEM, XRD, and ICP. Results show that the morphology of the catalysts, i.e., surface area, pore volume, pore size distribution, crystallite sizes, and promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In the present study, all MPdA catalysts were synthesized in a single step by mixing their precursors; hence the distribution and particle sizes of Pd may also depend on the synthesis procedure as well as on the properties of the Al 2 O 3 . Therefore, the reality of smaller-size Pd particles in all the MPdA catalysts, irrespective of the calcination temperature, may result from the solvent deficient environment generated in the synthesis procedure, which inhibits the migration of reagent materials that would subsequently terminate the nucleation of nanoparticles [27,28]. It was established in our previous study that PdO and γ-Al 2 O 3 were the final phases of their precursors (i.e., boehmite (AlOOH) for Al and PdO, Pd(NH 3 ) 2 (NO 2 ) 2 , and (Pd(NO 2 )(NH 3 ) 3 ) 2 (Pd(NH 3 ) 4 (NO 3 ) 4 ) for Pd) in the MPdA catalyst after calcination [9].…”
Section: Influence Of Calcination Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all MPdA catalysts were synthesized in a single step by mixing their precursors; hence the distribution and particle sizes of Pd may also depend on the synthesis procedure as well as on the properties of the Al 2 O 3 . Therefore, the reality of smaller-size Pd particles in all the MPdA catalysts, irrespective of the calcination temperature, may result from the solvent deficient environment generated in the synthesis procedure, which inhibits the migration of reagent materials that would subsequently terminate the nucleation of nanoparticles [27,28]. It was established in our previous study that PdO and γ-Al 2 O 3 were the final phases of their precursors (i.e., boehmite (AlOOH) for Al and PdO, Pd(NH 3 ) 2 (NO 2 ) 2 , and (Pd(NO 2 )(NH 3 ) 3 ) 2 (Pd(NH 3 ) 4 (NO 3 ) 4 ) for Pd) in the MPdA catalyst after calcination [9].…”
Section: Influence Of Calcination Temperaturementioning
confidence: 99%
“…In the SDP method, when the metal nitrate reacts with ammonium bicarbonate, they form a solvent deficient environment which then yields an intermediate hydroxide product (e.g. metal hydroxide or metal oxide hydroxide) and an ammonium nitrate (NH 4 NO 3 ) byproduct [27,28]. During aggregation in the solvent deficient environment, the spectator ions or molecules (NH 4…”
Section: Influence Of Calcination Timementioning
confidence: 99%
“…4 The Langmuir-Hinshelwood-Hougen-Watson (LHHW) type approach has been found successfully in describing many different heterogeneous catalytic reactions such as methylcyclohexane dehydrogenation over Pt/Al 2 O 3 catalyst, the oxidation of nitric oxide over carbon catalysts, esterification of acetic acid with ethanol over ion exchange resins etc. 10 Although the efforts of using complex LHHW mechanistic approach with the aid of genetic algorithm (GA) for data regression provide the robust solutions, [11][12][13][14][15] the limitations pertaining to the debatable mechanistic elementary reactions, difficulties of being both physical and statistical relevance, tedious computational times, and complexity of the established kinetic system based upon proposed mechanistic elementary reactions, all pose persistent challenges on designing and sizing the catalytic process involving the complex kinetics in the realistic scenario. 10 Although the efforts of using complex LHHW mechanistic approach with the aid of genetic algorithm (GA) for data regression provide the robust solutions, [11][12][13][14][15] the limitations pertaining to the debatable mechanistic elementary reactions, difficulties of being both physical and statistical relevance, tedious computational times, and complexity of the established kinetic system based upon proposed mechanistic elementary reactions, all pose persistent challenges on designing and sizing the catalytic process involving the complex kinetics in the realistic scenario.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Among them, Fischer-Tropsch (FT) synthesis is one of the extensively investigated area using the LHHW approach. 10 Although the efforts of using complex LHHW mechanistic approach with the aid of genetic algorithm (GA) for data regression provide the robust solutions, [11][12][13][14][15] the limitations pertaining to the debatable mechanistic elementary reactions, difficulties of being both physical and statistical relevance, tedious computational times, and complexity of the established kinetic system based upon proposed mechanistic elementary reactions, all pose persistent challenges on designing and sizing the catalytic process involving the complex kinetics in the realistic scenario. [16][17][18][19][20][21][22][23][24][25] Due to its inherent features of fast converge, less computational time together with equipped statistical analysis, the hybrid ANNs-RSM has been successfully implemented into many practical applications such as investigation of the flexible mechanism considering friction dynamics in lubricating industry, 26 structural reliabilities studies, 27 and optimization of biohydrogen productions etc.…”
Section: Introductionmentioning
confidence: 99%
“…3. Brunner and coworkers prepared iron Fischer-Tropsch catalysts by using solvent-deficient precipitation, focusing on the impacts of different catalyst preparation steps [3]. They found that the key steps in catalyst synthesis were whether the precursor catalyst was washed, how the promoted was added, and the drying condition.…”
mentioning
confidence: 99%